2002
DOI: 10.1079/nrr200238
|View full text |Cite
|
Sign up to set email alerts
|

Idiosyncratic nutrient requirements of cats appear to be diet-induced evolutionary adaptations

Abstract: Cats have obligatory requirements for dietary nutrients that are not essential for other mammals. The present review relates these idiosyncratic nutritional requirements to activities of enzymes involved in the metabolic pathways of these nutrients. The high protein requirement of cats is a consequence of the lack of regulation of the aminotransferases of dispensable N metabolism and of the urea cycle enzymes. The dietary requirements for taurine and arginine are consequences of low activities of two enzymes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
147
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(161 citation statements)
references
References 101 publications
(91 reference statements)
2
147
0
Order By: Relevance
“…Note that this does not translate into the conclusion that all carnivores should be fed the same diet; differences in adaptations to the physical characteristics or the micronutrient composition of the natural diet need to be considered [e.g. differences in the requirement of taurine, vitamins, or polyunsaturated fatty acids, Morris, 2002]. And although this study is concerned with digestive physiology rather than behavioral needs, behavioral aspects of the feeding of captive wild carnivores should not be dismissed [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Note that this does not translate into the conclusion that all carnivores should be fed the same diet; differences in adaptations to the physical characteristics or the micronutrient composition of the natural diet need to be considered [e.g. differences in the requirement of taurine, vitamins, or polyunsaturated fatty acids, Morris, 2002]. And although this study is concerned with digestive physiology rather than behavioral needs, behavioral aspects of the feeding of captive wild carnivores should not be dismissed [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The high protein requirement of the feline, thought to be for N rather than essential amino acids, is reported to be due to a permanently high hepatic capacity for amino acid catabolism and ureagenesis (Rogers et al 1977;Morris, 2002). This confers a limited ability to adapt to a low-protein diet with a consequent negative N balance.…”
Section: Discussionmentioning
confidence: 99%
“…Cats (Felis silvestris catus ) are generally thought to have a high requirement for dietary protein compared with both omnivores and herbivores (Rogers & Morris, 1980) and this has been attributed to the apparent inability of the hepatic catabolic, ureagenic and gluconeogenic enzymes of the feline to adapt to dietary protein intake (Rogers et al 1977;Morris, 2002). However, several groups have since reported that the cat does adapt to dietary protein in vitro in terms of both ureagenesis and gluconeogenesis (Kettlehut et al 1980;Silva & Mercer, 1985).…”
mentioning
confidence: 99%
“…3(a), step II), which can directly be used for intramitochondrial gluconeogenesis. This enzymic adaptation appears to be part of a long list of adaptations in this species, such as cysteine dioxygenase and cysteinesulfinate decarboxylase (taurine synthesis), pyrroline-5-decarboxylase and ornithine aminotransferase (citrulline synthesis), dioxygenase (retinol synthesis), glucokinase (glucose metabolism), 7-hydroxycholesterol-D7 reductase (25-hydroxycholesterol synthesis) and picolinic carboxylase (nicotinic acid synthesis) (39,98) . Dietary factors influencing endogenous urinary oxalate synthesis.…”
Section: Urinary Oxalatementioning
confidence: 99%